The impact of graduate student goal orientation on design projects. (4th May 2022) - Graff, Daniel
Abstract : Many universities offer courses in which students from various disciplines form teams to work on complex design challenges. Despite the importance of such teams for engineering design education, very little is known about them. This study explores the impact of graduate student goal orientations (mastery, performance-proof, and performance-avoidance) on course performance (team performance and peer assessment) via functional team member selection. The study examined 122 teams and found that students with performance-proof and performance-avoidance orientations are more likely to form functionally homogenous teams. However, there is no significant relationship between a mastery goal orientation and functional team diversity. Furthermore, the results indicate that functional team diversity is a double-edged sword for course performance, insofar as it has a positive impact on team performance, but also a negative effect on peer assessment. In addition, both performance goal orientations (performance-proof and performance-avoidance) have a negative effect via functional diversity on team performance and a positive effect on peer assessment. The findings advance our understanding of team member selection by graduate students and the effect thereof on course performance. Hence they may assist in developing future tools and processes to enhance learning by engineering design students in interdisciplinary design projects.